1987
DOI: 10.1085/jgp.90.5.651
|View full text |Cite
|
Sign up to set email alerts
|

A derivative of amiloride blocks both the light-regulated and cyclic GMP-regulated conductances in rod photoreceptors.

Abstract: Vertebrate rod photoreceptors in the dark maintain an inward current across the outer segment membrane. The photoresponse results from a light-induced suppression of this dark current. The light-regulated current is not sensitive to either tetrodotoxin or amiloride, potent blockers of Na+ channels. Here, we report that a derivative of amiloride, 3',4'-dichlorobenzamil (DCPA), completely suppresses the dark current and light response recorded from rod photoreceptors. DCPA also blocks a cyclic GMP-activated curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 31 publications
(54 reference statements)
0
27
1
Order By: Relevance
“…Thus, blockage of the photocurrent by intracellular L-cis-diltiazem exhibits the same voltage dependence as that observed with extracellular application. The amiloride derivative 3',4'-dichlorobenzamil applied extracellularly suppresses the light-sensitive current of amphibian rods at concentrations that are approximately one order of magnitude lower than those required by L-cis-diltiazem (Nicol et al 1987). Figure 7A illustrates t interrupted, the response regained its original amplitude.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, blockage of the photocurrent by intracellular L-cis-diltiazem exhibits the same voltage dependence as that observed with extracellular application. The amiloride derivative 3',4'-dichlorobenzamil applied extracellularly suppresses the light-sensitive current of amphibian rods at concentrations that are approximately one order of magnitude lower than those required by L-cis-diltiazem (Nicol et al 1987). Figure 7A illustrates t interrupted, the response regained its original amplitude.…”
Section: Resultsmentioning
confidence: 94%
“…The amiloride derivative 3',4'-dichlorobenzamil proved to be a more powerful blocker, with a K% in the vicinity of 5/M. This substance has been reported to inhibit the Nat-Ca2P exchanger of secretory cells (Kaczorowski et al 1985) and vertebrate rods (Nicol et al 1987), as well as L-type voltagedependent Ca!+ channels (Suarez-Kurtz & Kaczorowski, 1988;Garcia et al 1990); however, the half-maximal concentration for blockage of the light-sensitive, cGMP-gated conductance of amphibian and of scallop photoreceptors is approximately 10-fold lower, suggesting a high specificity of action. Amiloride was also capable of antagonizing the photoresponse but with a potency approximately 100-fold lower than its derivative.…”
Section: Resultsmentioning
confidence: 98%
“…The dark-current of vertebrate photoreceptor cells (rod outer segments) is blocked by the amiloride analog DCPA (apparent inhibition constant 1 /xM). However, this compound appears to block the cGMPactivated channels from the cytosolic side of the membrane [51]. It is not known whether the darkcurrent is affected by amiloride itself.…”
Section: Amilor1dementioning
confidence: 99%
“…For instance, the Na/Ca-exchanger is blocked with an apparent inhibition constant of 1-2 mM [34]. However, the sidechain modified analog 3',4'-dichlorobenzamil (DCPA) inhibits Na/Ca-exchange with an apparent inhibition constant in the range 15-50/xM [34,51].…”
Section: Amilor1dementioning
confidence: 99%
“…Very little is known about the pharmacology of NCKX proteins. Earlier work on NCKX1 in retinal rod outer segments showed that 3',5' dichlorobenzamil, 36 tetracaine and L-cis diltiazem 4 could block forward exchange at relatively high concentrations, while the same compounds were much more effective in inhibiting cGMP-gated channels present in this preparation. This implies that these compounds are unlikely to serve as useful diagnostics to detect NCKX activity.…”
Section: Functional Characteristicsmentioning
confidence: 80%